1996
DOI: 10.1074/jbc.271.4.2033
|View full text |Cite
|
Sign up to set email alerts
|

The Amino-terminal One-third of αIIb Defines the Ligand Recognition Specificity of Integrin αIIbβ3

Abstract: The integrin alpha subunits play a major role in the regulation of ligand binding specificity. To gain further insight into the regions of the alpha subunits that regulate ligand specificity, we have utilized alpha v / alpha IIb chimeras to identify regions of alpha IIb that when substituted for the homologous regions of alpha v switched the ligand binding phenotype of alpha v beta 3 to that of alpha IIb beta 3. We report that the ligand recognition specificity of beta 3 integrins is regulated by the amino-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
59
0
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 56 publications
2
59
0
1
Order By: Relevance
“…Employing ␣v/␣IIb chimeras, it has been reported that ligand recognition specificity of ␣ IIb ␤ 3 is regulated by the amino-terminal one third of the ␣ subunit that contains the amino-terminal 140 residues and first 2 divalent cation binding repeats of ␣IIb. 46 Because missense mutations in ␤ 3 affect the expression and function of ␤ 3 integrins differently, the key structure should lie in the ␣ subunits. Further investigation of the structures in the ␣ subunits that regulate the biosynthesis of the ␤ 3 integrins is underway.…”
Section: Discussionmentioning
confidence: 99%
“…Employing ␣v/␣IIb chimeras, it has been reported that ligand recognition specificity of ␣ IIb ␤ 3 is regulated by the amino-terminal one third of the ␣ subunit that contains the amino-terminal 140 residues and first 2 divalent cation binding repeats of ␣IIb. 46 Because missense mutations in ␤ 3 affect the expression and function of ␤ 3 integrins differently, the key structure should lie in the ␣ subunits. Further investigation of the structures in the ␣ subunits that regulate the biosynthesis of the ␤ 3 integrins is underway.…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence that the predicted loops between N-terminal repeats 2 and 3 (W3 4-1 loop) and within repeat 3 (W3 2-3 loop) are important for ligand binding in non-I-domain ␣subunits. 18,[40][41][42][43] Previous studies have shown that the N-terminal one-third of the ␣ subunit regulates ligand-recognition specificity of ␤ 3 integrins 44 and that residues 139-167 in ␣ v corresponding to the W3 4-1 loop are a cross-linking site for RGD peptides. 21 However, the ␣ v Y178 identified in this study is located in the predicted W3 2-3 loop, and none of the alanine substitutions within the W3 4-1 loop examined impaired ligand binding.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that the N-terminal regions of both the a and ~ subunits are involved in ligand binding [5][6][7][8][9], but the lack of structural information for either region means that interpretation of the role of specific residues involved in ligand binding is very difficult. The exception to this lack of information is the subset of integrin a subunits which contain von Willebrand factor A-type domains (known as VWFA domains, sometimes referred to as A-or I-domains).…”
Section: Introductionmentioning
confidence: 99%